2021
DOI: 10.5603/gp.a2021.0210
|View full text |Cite
|
Sign up to set email alerts
|

P1 promoter IGF-1 polymorphism and IGF-1, IGF-R, LSF, and TSG 101 expression profile in endometriosis

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Ovulation sources the follicular ingredients into the peritoneal fluid and constitutes the main contents of the peritoneal fluid, which is regarded as an ovarian exudate [ 37 , 38 ]. The epithelium of the endometriosis lesion expresses high levels of IGF-1R and c-MET, the receptor for IGF1/2 and HGF, respectively [ 39 , 40 ]. Previous studies have found a higher level of IGF [ 41 ] and HGF [ 39 ] in the peritoneal fluid from endometriosis patients than in those without endometriosis, and the level of HGF correlated positively with the revised American Society of Reproductive Medicine score.…”
Section: Missing Link 1: Ovulation Is An Overlooked Etiological Facto...mentioning
confidence: 99%
“…Ovulation sources the follicular ingredients into the peritoneal fluid and constitutes the main contents of the peritoneal fluid, which is regarded as an ovarian exudate [ 37 , 38 ]. The epithelium of the endometriosis lesion expresses high levels of IGF-1R and c-MET, the receptor for IGF1/2 and HGF, respectively [ 39 , 40 ]. Previous studies have found a higher level of IGF [ 41 ] and HGF [ 39 ] in the peritoneal fluid from endometriosis patients than in those without endometriosis, and the level of HGF correlated positively with the revised American Society of Reproductive Medicine score.…”
Section: Missing Link 1: Ovulation Is An Overlooked Etiological Facto...mentioning
confidence: 99%